1995
DOI: 10.1128/jb.177.1.144-151.1995
|View full text |Cite
|
Sign up to set email alerts
|

Two different Escherichia coli proP promoters respond to osmotic and growth phase signals

Abstract: proP of Escherichia coli encodes an active transport system for proline and glycine betaine which is activated by both hyperosmolarity and amino acid-limited growth. proP DNA sequences far upstream from the translational start site are strongly homologous to the promoter of proU, an operon that specifies another osmoregulated glycine betaine transport system. Mutation and deletion analysis of proP and primer extension experiments established that this promoter, P1, was responsible for proP's strong expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
76
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 38 publications
(52 reference statements)
3
76
0
Order By: Relevance
“…We have demonstrated in this in vitro study the existence of two promoters, P1 and P2, for proU. We have also confirmed the participation of E S in proU transcription, which has been documented for a variety of other osmoresponsive operons in E. coli (17,18,24,35,58). Three effects of potassium glutamate on proU transcription in vitro were identified, namely, (i) direct activation of P1 transcription by E S (and P2 transcription by E 70 ), (ii) inhibition of P1 transcription by E 70 (both together leading to the increase in selectivity for E S at P1), and (iii) antagonism of inhibition of H-NS.…”
supporting
confidence: 65%
“…We have demonstrated in this in vitro study the existence of two promoters, P1 and P2, for proU. We have also confirmed the participation of E S in proU transcription, which has been documented for a variety of other osmoresponsive operons in E. coli (17,18,24,35,58). Three effects of potassium glutamate on proU transcription in vitro were identified, namely, (i) direct activation of P1 transcription by E S (and P2 transcription by E 70 ), (ii) inhibition of P1 transcription by E 70 (both together leading to the increase in selectivity for E S at P1), and (iii) antagonism of inhibition of H-NS.…”
supporting
confidence: 65%
“…A search for consensus sequences of the osmoresponsive promoters for the compatible solute transport systems proU, prop and o p u A (Mellies et al, 1994(Mellies et al, ,1995Kempf & Bremer, 1995) revealed no matches. As several osmoregulated genes in non-halophiles, including the genes for the biosynthesis of trehalose, are known to be under the control of as-dependent promoters (Strram & Kaasen, 1993;Gordia & Gutierrez, 1996;Manna & Gowrishankar, 1994;Mellies et al, 1995), we also conducted a search for consensus sequences of these (Strram & Kaasen, 1993), but were unable to find any matches. Instead, we found a sequence similar to the consensus for oB of Bacillus subtilis (Fig.…”
Section: Ectoine Synthesizing Capacity Of Deletion Derivatives Of Posmllmentioning
confidence: 99%
“…Subsequently, these charged solutes are partially replaced by endogenous trehalose or compatible solutes accumulated from the medium, if present (Dinnbier et al, 1988). Most studies at the molecular level have so far focused on the various solute uptake systems of E. coli (Altendorf & Epstein, 1993;Mellies et al, 1995;Gowrishankar & Manna, 1996). The only investigations concerned with the biosynthesis of compatible solutes covered choline oxidation and trehalose synthesis (Lamark et al, 1996;Strarm & Kaasen, 1993).…”
mentioning
confidence: 99%
“…1A). Transcription from the P2 promoter is dependent on s and Fis (32,47). During late exponential phase, s levels are increasing while Fis levels are decreasing (1,21,27,36).…”
mentioning
confidence: 99%
“…The ProP transporter appears to function as a (compatible solute ϩ H ϩ )/K ϩ antiporter (29). ProP activity can be rapidly stimulated by osmotic shock (17,18,30) by enhancing transcription (13,22,32,35) or by posttranslational mechanisms (34).…”
mentioning
confidence: 99%